Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1136/archdischild-2011-301589
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of fetal trisomy 18 after prenatal diagnosis

Abstract: These data provide reliable information for parental counselling pertaining to risk of intrauterine death when trisomy 18 is diagnosed prenatally. These findings suggest that long-term survival implications for trisomy 18 are different when it is diagnosed prenatally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 6 publications
(14 reference statements)
0
29
0
1
Order By: Relevance
“…29,[44][45][46][47] In Brazil, there is a public policy of screening for aneuploidy, therefore, cases with ultrasound changes in the morphological examination from the first and second trimester are referred to tertiary care centers, such as the HC-FMUSP, a situation similar to that described by Yamanaka et al 44 in a study published in Japan in 2006. In 2013, Loane et al, 38 in a study using data from the European Surveillance of Congenital Anomalies (Eurocat), reported that 58% of cases with prenatal diagnosis of T21 are identified in the ultrasound screening at the first trimester, and 16% after combined screening (biochemical and ultrasound).…”
Section: Methodsmentioning
confidence: 66%
See 2 more Smart Citations
“…29,[44][45][46][47] In Brazil, there is a public policy of screening for aneuploidy, therefore, cases with ultrasound changes in the morphological examination from the first and second trimester are referred to tertiary care centers, such as the HC-FMUSP, a situation similar to that described by Yamanaka et al 44 in a study published in Japan in 2006. In 2013, Loane et al, 38 in a study using data from the European Surveillance of Congenital Anomalies (Eurocat), reported that 58% of cases with prenatal diagnosis of T21 are identified in the ultrasound screening at the first trimester, and 16% after combined screening (biochemical and ultrasound).…”
Section: Methodsmentioning
confidence: 66%
“…In the medical literature, the frequency of structural abnormalities in fetuses with T13/18 is high, and is found in 80 to 100%. 26,32,47,[54][55][56] In this study, of the 9 fetuses with prenatal diagnosis of T13/18 that showed no MF at the time of the karyotype studies, 6 underwent karyotype studies using CVS in the first trimester, showing an increased NT as an indication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians must be aware of the possibility of pregnancies progressing to term, and ending in a live birth. 69 Parents, obstetricians, and neonatologists must therefore plan for the perinatal care of these pregnancies, either when couples decline the offer of pregnancy termination, or when clinicians cannot offer this option. Parents who choose to continue the pregnancy may wish to discuss what postnatal care will be offered to 'survivors' and clinicians should discuss with their colleagues treatment options for those children that do not die during or soon after birth.…”
Section: Trisomy 18 (Edwards Syndrome)mentioning
confidence: 99%
“…Nelson et al [40] state "although diagnoses of trisomy 13 and 18 are generally assumed to be fatal within days to weeks after birth, a small but significant subgroup of children with trisomy 13 and 18 are alive over the age of 1 year, and at least some of these children receive substantial inpatient hospital care" (p. 874) Yates et al [41] point to a shift in interventions to address cardiac anomalies based on parent request. Yet, the impact of these studies is minimized by empirical reports emphasizing early mortality [42].…”
Section: Offering a Positive Viewpoint And Associated Recommendationsmentioning
confidence: 99%